Age May Be the Only Variable Effecting Microhematuria Prevalance in Pelvic Organ Prolapse - Ayse Filiz Gokmen Karasu; Serdar Aydin; Ilknur Adanir; Gulsah Ilhan; Senad Kalkan; Seda Ates (Medical Network, 2018)
Objective: We aimed to estimate the prevalence of microscopic hematuria in women with pelvic organ descent and compare the results in terms of severity and accompanying urinary symptoms. We hypothesized that microhematuria incidence would be higher in advanced prolapse and accompanying urinary symptoms. Study Design: Women who presented to our clinic from January 2013 to July 2016 were analyzed using our electronic medical record system. Those who were classified in the system under the "N81: female genital prolapse" code were included. Records were checked to certify that samples were acquired properly. Urogynecological examinations were performed by specialist gynecologists and documented according to the international continence society classification system. After ruling out urinary tract infections urinalysis was performed by an integrated system composed of an urine strip analyzer and a sediment autoanalyzer. Results: Gravidity, parity, menopause onset, smoking status and presence of systemic disease were similar for both groups. Women in the hematuria group were older (p<0.001). Hematuria prevalance was greater ininternational continence society Stage 3-4 anterior prolapse and total prolapse (p=0.03) compared to early stage prolapse. However after logistic regression analysis; age was the only factor left in association with hematuria. Conclusions: Women who were older and with advanced stage prolapse ( ≥ international continence society stage 3) were more likely to have microscopic hematuria. Urine tests are requested routinely in the work-up of urogynecological patients. As the prevalance is microhematuria is high in this population; we believe that evidence based algorithms should be set as guidelines when hematuria is encountered in patients with organ prolapse.